Counseling Opportunity Structures: Explaining College-Going Using a Typology of School-Level Opportunity Structures. Issue 1 (January 2020) - Rangel, Virginia Snodgrass; Ballysingh, Tracy A.
This article contributes to our understanding of the gap in college access by examining (a) the extent to which and (b) how high school counseling focused on college broadens access. We extend Engberg and Gilbert's typology of schools based on high school counseling norms and resources. Using recent data from the High School Longitudinal Study of 2009, we identified three types of schools: norm-driven, resource-rich, and divergent.